"Coding" and "Decoding": hypothesis for the regulatory mechanism involved in heparan sulfate biosynthesis. (16th June 2016) - Zhang, Xu; Wang, Fengshan; Sheng, Juzheng
Highlights: Two major steps, "coding" and "decoding", are involved in the biosynthesis of HS. "Coding" is based on the distribution of sulfate moieties on the glucosamine. "Code" is created by N-deacetylase/N-sulfotransferase, which has four isozymes. C5-epimerase and O-sulfotransferases recognized the "Code". This mechanism regulates chemical structure and biological activity of HS. Graphical abstract: Abstract: Heparan sulfate (HS) is widely distributed in mammalian tissues in the form of HS proteoglycans, which play essential roles in various physiological and pathological processes. In contrast to the template-guided processes involved in the synthesis of DNA and proteins, HS biosynthesis is not believed to involve a template. However, it appears that the final structure of HS chains was strictly regulated. Herein, we report research based hypothesis that two major steps, namely "coding" and "decoding" steps, are involved in the biosynthesis of HS, which strictly regulate its chemical structure and biological activity. The "coding" process in this context is based on the distribution of sulfate moieties on the amino groups of the glucosamine residues in the HS chains. The sulfation of these amine groups is catalyzed by N -deacetylase/ N -sulfotransferase, which has four isozymes. The composition and distribution of sulfate groups and iduronic acid residues on the glycan chains of HS are determined by several other modification enzymes, which can recognize these coding sequences (i.e., the "decoding" process). The degree and pattern of the sulfation and epimerization in the HS chains determines the extent of their interactions with several different protein factors, which further influences their biological activity.